Online Learning: A Pilot Study of Teaching Fundamental Courses in Vietnam - Thi Van Pham, A. (Association for Computing Machinery, 2020)
Online learning (OL) has been employed in all levels of education all over the world for decades. It brings back a number of benefits for three main stakeholder groups of education-students, lecturers and administrators. However, OL poses a lot of challenges compared to traditional learning or blended learning (BL), especially in Vietnam education context. In this paper, the authors conducted the study on administrators, lecturers and student's perceptions of the OL implementation in teaching Fundamental courses at a polytechnic in Vietnam. The primary data was collected via the online survey of 355 students in the Spring 2020 semester as well as the individual interviews with four lecturers and two administrators at the polytechnic. Basing on the data analysis, recommendations regarding course content and assessment, student-lecturer interaction and lecturers' incomes were offered to improve the quality of OL at the polytechnic in the long term. These findings in this study could be taken into consideration to develop and implement OL for other courses as well as look for the framework for the sustainable OL implementation at the polytechnic in the future. Â© 2020 ACM.